Asian independence leaders - Wakin, Eric (New York Facts on File, 1997)
Profiles nine men, including Sun Yat-sen of China, Gandhi of India, Ho Chi Minh of Vietnam, and Emilio Aguinaldo of the Philippines, who struggled to free their respective countries from colonial rule or monarchy.
Keywords: Nationalists -- Asia -- Biography -- Juvenile literature; Heads of state -- Asia -- Biography -- Juvenile literature; Heads of state -- Asia; Nationalists -- Asia; Revolutionaries -- Asia -- Biography -- Juvenile literature; Asia -- Biography